ANALISA KUALITAS PRODUK ZINC DIE CAST UNTUK MENURUNKAN TINGKAT REJECT DENGAN METODE SIX SIGMA (DMAIC) DI PT. TST: ANALISA KUALITAS PRODUK ZINC DIE CAST UNTUK MENURUNKAN TINGKAT REJECT DENGAN METODE SIX SIGMA (DMAIC) DI PT. TST - Aprina, Budi; Rudy, Anthon (Universitas Pamulang, 2025)
Micro and small businesses engaged in ice cube production are highly dependent on the reliability of their production machines. A decrease in machine performance can have a direct impact on product quality and quantity. This study aims to analyze the actual condition of the machine, determine the appropriate type of maintenance, and apply the Total Productive Maintenance (TPM) concept to improve machine effectiveness. The methods used include direct inspection, cycle time measurement, and Overall Equipment Effectiveness (OEE) calculation. The results showed that the OEE value was at 76.12%, with an availability value of 91.67%, a performance rate of 92.31%, and a quality rate of 90%. This value indicates that the machine is in fairly good condition but needs periodic preventive repairs. Maintenance recommendations include the implementation of Autonomous Maintenance, operator training, and a structured maintenance schedule. Keywords: SME,Overall Equipment , Total Productive Maintenance